High Titer Inhibitor-Acquired Hemophilia A Treated With Human FVIII Concentrate in Limited Resource: A Case Report - Kandinata, Stefanus Gunawan; Bintoro, Ugroseno Yudho (Malaysian Journal of Medicine and Health Sciences, 2022)
Acquired hemophilia A (AHA) is a rare condition that affects one in a million people each year, and there are not many diagnostics or therapeutic agents available for treatment due to its rarity. This is a case report of a 61-year-old woman who presented with a spontaneous subcutaneous hematoma and multiple extensive bruises in her extremities. There was no prior history of bleeding disorders, and the laboratory results showed an isolated aPTT prolongation with no correction after mixing studies, and a reduction in FVIII activity level along with a high FVIII inhibitor titer (928BU). Furthermore, the diagnosis of idiopathic AHA was made after other secondary causes had been ruled out, and the patient received human FVIII concentrate instead of bypassing agents due to its availability. The patient still experienced clinical improvement despite using this alternative. AHA is currently managed using both hemostasis agents and inhibitor eradication, and they come with several limitations. Human FVIII concentrate therapy is still an option in situations with limited resources, even though it is not recommended in patients with high inhibitor titer levels.